Quantitative Analysis of Attention and Detection Signals During Visual Search - Shulman, Gordon L.; McAvoy, Mark P.; Cowan, Melanie C.; Astafiev, Serguei V.; Tansy, Aaron P.; d'Avossa, Giovanni; Corbetta, Maurizio (Journal of neurophysiology, 2003)
Prior work has distinguished regions in the intraparietal sulcus (IPs) and frontal eye field (FEF) involved in the voluntary control of attention, from more ventral regions in the temporoparietal junction (TPJ) involved in target detection. The present results show that when subjects search for and detect a visual target stimulus among nontargets, these regions show sensory-, search-, and detection-related signals that both confirm and refine these functional distinctions. The different signals were isolated by an additive model that accounted for a large fraction of BOLD (blood oxygenation level-dependent) signal modulation over the brain. Both IPs and FEF were activated during search through nontargets, consistent with a role in maintaining attention-related signals during search. However, unlike FEF, IPs also showed stimulus-related activations, and may combine signals related to sensory and task-dependent components of salience. Although IPs-FEF showed search-related activations, the TPJ was deactivated during search. TPJ activations were confined to detection-related signals. These results provide a much stronger dissociation between the TPJ and IPs-FEF than previous work, while indicating functional differences between frontal and parietal regions that are often coactivated in studies of attention. Finally, continuous flow models of information processing predict that during search, signals from missed targets should be fed from sensory to associative regions rather than being gated by the decision criterion. Correspondingly, missed targets significantly activated parietal (e.g., right TPJ) and frontal (e.g., anterior insula, anterior cingulate) regions, although with a smaller magnitude than detected targets. Surprisingly, many cortical regions showed equivalent signals from detected targets and the completion of target-absent trials, reflecting a widespread signal unrelated to motor execution.